Corporate governance mechanisms, firm’s characteristics and capital structure in Nigerian listed firms - Aminu Abdulrahim, Olayinka (2018)
Studies on the influence of corporate governance mechanisms on capital structure decisions in the emerging markets are still very limited. This study examined the influence of corporate governance mechanisms, firm characteristics and macroeconomic variables on capital structure of Nigeria non-financial listed firms. Unlike the vast majority of previous studies, this study employed panels corrected standard errors (PCSEs) model to analyse the relationship between corporate governance mechanism, firm characteristics and macroeconomic variables on capital structure of 106 Nigerian non-financial listed firms during the 2012 to 2016 period. The model was robust to any unit heterokedasticity and possible contemporaneous correlation issues. The results revealed that board structure (board size, board meeting and board independence) and ownership structure (managerial and institutional ownership) were negatively related to the total debt ratio, whereas blockholder ownership and firm characteristics (firm age, firm size and firm growth) were positively related. In addition, the choice of external auditor (B4 audit firm) had no significant relationship to the total debt ratio of the sample firms. Control variables namely GDP and inflation rate were negatively related to the total debt ratio, whereas bank lending rate was positively related. Corporate governance in Nigeria is at its developing stage, the firms still has weak corporate governance mechanisms as compared to firms in developed countries. The study found that, corporate governance attributes and firm characteristics partly explained the capital structure of Nigeria firms. Nigeria firms’ manager should be aware of the benefits on the implementation of effective corporate governance monitoring mechanisms. An effective implementation of the Corporate Governance Code 2011 issued by Security and Exchange Commission should improve the efficiency and effectiveness of Nigeria firms and the stock markets. To the author’s best knowledge, this study is among the few studies that utilized panels corrected standard errors model in providing evidence of the influence of corporate governance mechanisms and firm characteristics on capital structure in Nigeria.